A dynamical interpretation of the intensification of the winter North Atlantic jet stream in reanalysis - Hermoso, Alejandro; Rivière, Gwendal; Harvey, Ben; Methven, John; Schemm, Sebastian (Journal of Climate, 2024)
International audience Jet streams play an important role in determining weather variability and extremes. A better understanding of the mechanisms driving long-term changes in the jet is essential to successfully anticipate extreme meteorological events. This study analyzes the intensification trend of the North Atlantic jet using the ERA5 reanalysis and investigates the dynamical mechanisms involved. The results highlight the importance of an increase in diabatic heating in the free troposphere below the jet entrance over the Gulf Stream sector. This change in diabatic heating modifies the jet directly and produces a local intensification and a slight poleward shift. A two-dimensional frontal-geostrophic model illustrates this mechanism by considering the enhanced diabatic heating associated with the baroclinic growth of extratropical cyclones. The change in diabatic heating also affects the jet indirectly by increasing the mean baroclinicity and subsequent eddy momentum flux convergence. This indirect mechanism has also an effect downstream, where there is an acceleration of the jet core and reduced westerlies along the flanks, reducing the width of the jet. An idealized warming experiment confirms this mechanism by determining the jet response downstream of an idealized land-sea contrast. Finally, using a single-model ensemble of fully-coupled climate simulations, we show that the differences in the evolution of the North Atlantic jet are related to the latitude of the increase in baroclinicity, which has a large spread. What emerges from the model hierarchy is a consistent dynamical chain of mechanisms associated with the intensification trend of the North Atlantic jet stream.